2021
DOI: 10.3390/antibiotics10111397
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Tetracycline, Oxytetracycline, Sulfadiazine, Norfloxacin, and Enrofloxacin in Swine Manure Using a Coupled Method of On-Line Solid-Phase Extraction with the UHPLC–DAD

Abstract: The use of various veterinary antibiotics (VAs) in animal husbandry raises serious concerns about the development of antibiotic resistance. Antibiotics such as tetracycline, oxytetracycline, sulfadiazine, norfloxacin, and enrofloxacin are the most frequently used antimicrobial compounds in animal husbandry and generate large eco-toxicological effects; however, they are still difficult to determine in a complex matrix such as swine manure. This study has developed an effective method for detecting five VAs in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…High-performance liquid chromatography (HPLC) in the reverse-phase mode, with different detection modes, is commonly used to determine veterinary antibiotics. 4 , 26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-performance liquid chromatography (HPLC) in the reverse-phase mode, with different detection modes, is commonly used to determine veterinary antibiotics. 4 , 26 …”
Section: Methodsmentioning
confidence: 99%
“…Environmental Health Insights detection modes, is commonly used to determine veterinary antibiotics. 4,26 Detection of tetracycline residues using TLC. Thin Layer Chromatography (TLC) was used for the detection of tetracycline residues following the recommended techniques.…”
mentioning
confidence: 99%
“…Antibiotics, which are used for the treatment of bacterial infections, are based on a range of applications classified into narrow and broad spectrum. Narrow-spectrum antibiotics are designed to act upon a limited/targeted bacterial species, while broad-spectrum antibacterials have a wide range of application cutting across bacterial control in human and veterinary medicine . Studies have reported that an antibiotic could not be totally digested and is therefore released to the environment, , hence causing adverse environmental contamination and multidrug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its antibacterial properties and chemical durability, tetracycline (TC) is difficult to disintegrate spontaneously. 3 The residues have been shown to limit the growth of microorganisms in soil and water as well as induce the development of antibioticresistance genes. 7,8 The degradation of tetracycline has attracted many approaches due to challenging remedial difficulties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation